Qur’an Basic Game for Fun Learning Using Dynamic Weighting A Star - Faisal, Muhammad; Zakifardan, Ibnu; Eko W. R., Nonok (International Journal of Engineering and Technology, 2019)
The phenomenon of people who cannot read the Qur'an in Indonesia is quite significant. There are approximately 65 percent of Indonesian Muslims cannot read the Qur'anÂ andÂ 35 percent could read the Qur'an there are 21 percent who do not want to read the Quran (http://bimasislam.kemenag.go.id, 2015). Needed some strategies in learning to read the Qur'an. Along with technological developments in the media, then the media should be utilized as much as possible to support the learning of the Qur'an for Muslims in Indonesia. The combination of learning in synergy between classical learning method with learning methods based on Information Technology (IT) is expected to produce a model of learning to read the Qur'an so fun and not boring. In this study discusses the making of instructional media-based desktop and or android by combining computer technology with implementing Dynamic Weighting A Star Method on Non Player Character (NPC) so that its movement is better for NPC moves towards the target in accordance with the route that is generated by the algorithms.Â